Research on Automation of Operative Scheduling in Urban Public Transportation - Nagy, E.; Csiszár, Cs. (Acta Technica Jaurinensis, 2013)
Due to the large number of incidents in urban public transportation, work of traffic control dispatchers is indispensable. At certain times they are overstressed as they have to consider too many aspects according to the regulations and current information system does not provide enough help. Implementation of a decision support system would allow more efficient traffic and incident management. The aim of this paper is to study the possibilities of automation of operative scheduling. The goal is to analyze the tasks of dispatchers, determine the processes that could be substituted with decision support system and prepare the architecture of an IT system showing the database connection of decision support subsystem. The paper contains the operation and decision process on a flowchart that is the algorithm of the operative scheduling.